1996
DOI: 10.1002/(sici)1097-0045(199601)28:1<10::aid-pros2>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Dual monoclonal antibody immunoassay for free prostate-specific antigen

Abstract: Prostate‐specific antigen (PSA) is the most important tumor marker for early detection and monitoring of prostate cancer (PCa) patients. PSA is also elevated in many patients with benign prostatic hyperplasia (BPH). The study of the serum PSA forms, free PSA (f‐PSA) and PSA complexed with α1‐antichymotrypsin (PSA‐ACT), may improve the discrimination between PCa and BPH. An immunoassay specific for f‐PSA is reported with very low cross‐reactivity (0.7%) to PSA‐ACT. Serum specimens from BPH and PCa patients (det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…91 Seventeen of the 21 studies presented data on investigator-selected cut points. [73][74][75][76][77][78][79][80][81]83,84,[86][87][88][89][90] Table 1 shows the number of studies meeting the methodologic criteria used to evaluate validity and generalizability. Thirteen studies used needle biopsy as the single reference standard, but none of them used long-term clinical follow-up to define true negative test results.…”
Section: Resultsmentioning
confidence: 99%
“…91 Seventeen of the 21 studies presented data on investigator-selected cut points. [73][74][75][76][77][78][79][80][81]83,84,[86][87][88][89][90] Table 1 shows the number of studies meeting the methodologic criteria used to evaluate validity and generalizability. Thirteen studies used needle biopsy as the single reference standard, but none of them used long-term clinical follow-up to define true negative test results.…”
Section: Resultsmentioning
confidence: 99%
“…The improved diagnostic efficacy of the γ‐Sm/PSA ratio has been comprehensively demonstrated by an increased area under the ROC curve, where the entire spectrum of sensitivity and specificity pairs is graphed and compared with that of total PSA. A ROC curve analysis of the PSA F/T ratio has been report‐ ed to yield a greater area under the curve than total PSA alone, 19 although it has been suggested that free PSA values do not provide additional diagnostic benefit compared with total PSA in screening populations 20 . In the present study, the area under the ROC curve of PSA was 0.54 in this PSA range, sug‐ gesting that differentiation between BPH and prostate cancer using the PSA values is not significantly better than by chance (AUC = 0.5).…”
Section: Discussionmentioning
confidence: 99%
“…The amount of radioactivity bound to the bead is proportional to the amount of analyte present in the test sample, which is determined from a calibrated curve by using a linear or cubic spline equation to interpolate between calibrators. The current Tandem-R free PSA assay should not be confused with earlier research prototypes previously reported by Wang et al [19]. The research prototype was a sequential assay using streptavidin-coated microplates, biotinylated anti-free PSA (PSB999), and europium-labeled anti-PSA (PSM773).…”
Section: Materials and Methods Assay Methodsmentioning
confidence: 99%